Rītimukta kavitā, mukta racanā vidhāna - Candraśekhara, 1936- (Bhāratīya Grantha Niketana, 1979)
On the works of some medieval Hindi poets free from the contemporary stylistic (rīti) influence, 1700-1900; a study.